2013
DOI: 10.1242/dev.094961
|View full text |Cite
|
Sign up to set email alerts
|

Distinct temporal requirements for Runx1 in hematopoietic progenitors and stem cells

Abstract: SUMMARYThe transcription factor Runx1 is essential for the formation of yolk sac-derived erythroid/myeloid progenitors (EMPs) and hematopoietic stem cells (HSCs) from hemogenic endothelium during embryogenesis. However, long-term repopulating HSCs (LT-HSCs) persist when Runx1 is conditionally deleted in fetal liver cells, demonstrating that the requirement for Runx1 changes over time. To define more precisely when Runx1 transitions from an essential factor to a homeostatic regulator of EMPs and HSCs, and wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 39 publications
9
73
3
1
Order By: Relevance
“…8, top). This EMP population arises in the E8.25 yolk sac then seeds the fetal liver by E11.5, providing the first source of definitive erythroid progenitors prior to or coincident with colonization by distinct hematopoietic stem cell (HSC) sources (Chen et al, 2011;Lux et al, 2008;McGrath et al, 2011;Tober et al, 2013).…”
Section: Discussion Cellular and Mechanistic Aspects Of Erythroid/macmentioning
confidence: 99%
“…8, top). This EMP population arises in the E8.25 yolk sac then seeds the fetal liver by E11.5, providing the first source of definitive erythroid progenitors prior to or coincident with colonization by distinct hematopoietic stem cell (HSC) sources (Chen et al, 2011;Lux et al, 2008;McGrath et al, 2011;Tober et al, 2013).…”
Section: Discussion Cellular and Mechanistic Aspects Of Erythroid/macmentioning
confidence: 99%
“…Deletion of Runx1 in VE-Cadh + cells indicated that Runx1 is critically required in this population [28]. Although Runx1 expression continues in the emerging HSPCs and their offspring, spatiotemporal differences in the requirement for Runx1 and other members of the core-binding factor family were reported for these cells [28,57]. To obtain a transgenic Runx1 reporter that would allow for the positive identification of hemogenic endothelium, we had initiated studies into the transcriptional regulation of Runx1 and recently identified the Runx1 +23 enhancer.…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…Intra-aortic hematopoietic clusters appear transiently in the AGM region between embryonic days ∼10 and 12 in mouse (de Bruijn et al, 2000) and ∼4 and 6 weeks in human (Tavian et al, 1996). Runx1, a required transcription factor for the conversion of hemogenic endothelial cells to HSPCs (Chen et al, 2009;North et al, 1999), is first noted within a subset of endothelial cells in hemogenic vascular beds but then localizes to intra-aortic cluster cells (Tober et al, 2013). The transcription factor Sox17 has also been shown to be important in EHT (Clarke et al, 2013) and hematopoietic stem cell (HSC) survival (Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%